EWork and eBusiness in architecture, engineering and construction : proceedings of the European Conference on Product and Process Modelling 2010, Cork, Republic of Ireland, 14-16 September 2010 /: proceedings of the European Conference on Product and Process Modelling 2010, Cork, Republic of Ireland, 14-16 September 2010. (©2010) - Unknown
No abstract available